Spectroscopic methods in mineralogy and materials sciences - Henderson, Grant Stephen, 1956-; Neuville, Daniel R.; Downs, Robert T., 1955- (Mineralogical Society of America ; Geochemical Society, 2014)
A complement to Spectroscopic methods in mineralogy and geology, edited by Frank Hawthorne in 1988, vol. 18 of the Reviews in mineralogy series. This current work also updates many of the techniques mentioned in the original volume along with introducing new methods in spectroscopy that had developed in the past twenty-five years.
Keywords: Mineralogy, Determinative.; Spectrum analysis.; Minerals -- Spectra.; Materials -- Spectra.; Materials science.; Raman spectroscopy.; X-ray spectroscopy.; Infrared spectroscopy.; Ultraviolet spectroscopy.; Luminescence spectroscopy.; elektronické knihy; electronic books